Enhancing Students’ Speaking Skill through Digital Storytelling at State Islamic Senior High School 1 Surakarta - Cahyani, Nilam Lintang; Sari, Ayu Istiana (Universitas Pahlawan Tuanku Tambusai, 2026)
This study examines the use of digital storytelling to enhance students’ speaking skills in a formal classroom context, addressing the need for more engaging and effective speaking instruction at the tenth grade of MAN 1 Surakarta. Using a classroom action research design consisting of two cycles, data were collected through pre-test, post-test I, and post-test II, as well as observations and questionnaires. Descriptive analysis of test scores showed a steady improvement in students’ average speaking scores, increasing from 65 in the pre-test to 74 in Cycle I and reaching 85 in Cycle II. Qualitative findings revealed that digital storytelling supported speaking development by helping students organize ideas, apply appropriate past tense forms, improve pronunciation through repeated practice, and use vocabulary in meaningful contexts. Students also perceived digital storytelling as an appealing and accessible activity that reduced learning anxiety and increased participation. However, initial difficulties in organizing narratives and limited language control emerged as challenges that required teacher guidance. This study concludes that digital storytelling can serve as a meaningful medium for enhancing speaking skills in formal classroom settings when implemented with proper guidance and integrated with structured speaking activities.